Content of biogenic elements (zinc and copper) in soil component of bog biogeocenoses (on example of peatbog Zenginsky in Kirov region) - L. N. Shikhova; E. S. Gonina; A. N. Ulanov (Аграрная наука Евро-Северо-Востока, 2016)
Results of studying on influence of marsh field's economic use in central part of the Kirov region on its geochemical status are presented. Next variants have been chosen for research in 2012-2014: control - a virgin site of poorly drained non-mastered part of a bog; experimental - sites with different capacity of a residual peat layer (from 1.3-1.5 m to 0.5 m and less). On each of 14 sites soil cuts are put and peat samples on layers are selected. The content of total and mobile forms of elements is defined by a method of inversion voltamperometry. The conducted researches have shown that the copper and zinc content is minor and does not exceed average and background values, characteristic for various types of soils of area. The minimum content of elements is noted in a profile of a control site. The total content of copper has made from 0.90 mg/kg (on depth of 10-15 cm) to 0.28-0.14 mg/kg and lower (at level of 90-95 cm from a surface). The zinc content is also slightly and fluctuates in limits 0.16-0.17 mg/kg to 2.40-2.60 mg/kg on a profile. The content of elements rises in soils of mastered sites. For example, on a site prepared under tree-planting with capacity of a residual peat layer about 150 cm, total copper in peat is from 10.00-11.00 mg/kg to 33.0034.00 mg/kg, and zinc - from 17.00-39.50 mg/kg to 54.95-89.62 mg/kg. The content of mobile forms of metals in peat of the surveyed sites is minor. The minimum content - in a control site: zinc - 0.02-1.60 mg/kg and copper - from trace values up to 0.11-0.12 mg/kg. On the sites involved in economic activities increase of concentration of mobile forms of elements is revealed. The content of mobile zinc changes from 1.73 to 5.96 mg/kg, and copper - from 0.21 to 2.33 mg/kg. Almost on all sites the raised content of zinc and copper in the top soil horizons is noticed that is connected with biogenic accumulation of these elements by a vegetative cover. In some cases increase of concentration of elements on border of peat and mineral horizons is revealed. Development of peat fields leads to decrease in acidity of residual thickness of peat and formed on a place of a peatbog of soils as a result of a peat mineralization and rising of hard ground waters to a surface. In the given research pHKCi varies from 2.53-3.30 units on a control site to 4.47-6.67 in profiles of newly formed soils on the drained and developed sites.